FROM WHICH CENTURIES DO LEGENDS ORIGINATE? (Universal International Scientific Journal, 2026)
Legends are closely connected with history; however, unlike historical records,they are not fixed to exact dates. Instead, they develop gradually over long periods of time. Mostlegends begin as oral traditions and are later recorded in written form. Both English and Uzbeklegends trace their origins to ancient and medieval centuries, although they continued to evolve in laterhistorical periods
Keywords: legends; oral tradition; historical narratives